2013
DOI: 10.1017/s1743921313015974
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Studies on the Role of PAHs as DIB Carriers

Abstract: Abstract. The electronic spectroscopy of various polycyclic aromatic hydrocarbon (PAH) molecules has been studied in the laboratory at low temperatures using both molecular beam and matrix isolation spectroscopy techniques. While molecular beam spectra can be readily compared to astronomical observations, the band positions measured in Ne and Ar matrices are extrapolated to obtain rather good estimates for the same transitions in the gas phase. Absolute absorption cross sections are determined for gas-phase an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Because the maximum number of FAR of a helicene with experimental and theoretical absorbance spectral information available is 14 20 (see Table 1), the logarithmic trend established in Figure 2 is used in the following section to obtain the locations of p-bands for helicenes with 20−40 FAR. As discussed in the text surrounding Table 1, in the analysis of Figure 2, the locations of the p-bands for [10], [11], [12], [13], and [14]helicene provided by Birks and VanDer Donckt (as a note added like proof in advance of publication) in Obenland and Schmidt 20 with the maximum positive standard deviation (+0.06) are used to generate the maximum correlation coefficient of the resulting logarithmic trend, that is, close to one.…”
Section: Mathematical Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…Because the maximum number of FAR of a helicene with experimental and theoretical absorbance spectral information available is 14 20 (see Table 1), the logarithmic trend established in Figure 2 is used in the following section to obtain the locations of p-bands for helicenes with 20−40 FAR. As discussed in the text surrounding Table 1, in the analysis of Figure 2, the locations of the p-bands for [10], [11], [12], [13], and [14]helicene provided by Birks and VanDer Donckt (as a note added like proof in advance of publication) in Obenland and Schmidt 20 with the maximum positive standard deviation (+0.06) are used to generate the maximum correlation coefficient of the resulting logarithmic trend, that is, close to one.…”
Section: Mathematical Methodsmentioning
confidence: 97%
“…The study of the molecules that absorb electromagnetic radiation in the interstellar medium, for example, the carriers of the diffuse interstellar bands, DIBs, is the subject of ongoing research in the astrophysical community. Polycyclic aromatic hydrocarbons, PAHs, are considered potential carriers of the DIBs due to their verified presence in the interstellar medium and their striking stability in hostile atmospheres. , Numerous experimental and theoretical research efforts have helped to understand better the spectroscopy of PAHs and its relationship with the DIBs. Despite these facts, the identifications of the DIBs using spectral information from PAHs or PAHs derivatives have yet to be established.…”
Section: Introductionmentioning
confidence: 99%
“…The absorption measurements at seven wavelengths allowed us to evaluate AAEs in different wavelength intervals. The high optical band gap energies (Menon et al 2019) and absorption spectra (Huisken et al 2013) associated with non-refractory PAHs observed in the AMS (mainly PAHs with molecular masses of 202-300 Da) suggested that the non-refractory components that were removed in the TD would have only a minor contribution to absorption at wavelengths longer than 660 nm. Therefore, AAEs were evaluated in two wavelength intervals: the full 370-950 nm wavelength interval (AAE 370-950nm ) and for the 660-950 nm wavelength interval (AAE 660-950nm ).…”
Section: Aae In Different Wavelength Intervalsmentioning
confidence: 99%
“…9,10 Leaving aside their threat to humans health, 11 in the last years they have become highly relevant in industrial applications such as the production of dyes and pigments and pharmaceuticals 12,13 due to their photostability and photophysical properties. 14,15 These compounds have also been found to be a key piece in the understanding the chemistry of the interstellar medium. 16…”
Section: Introductionmentioning
confidence: 99%